2006
DOI: 10.1124/mol.105.018572
|View full text |Cite
|
Sign up to set email alerts
|

2-Cyano-3,12-dioxooleana-1,9(11)-diene-28-oic Acid Disrupts Microtubule Polymerization: A Possible Mechanism Contributing to Apoptosis

Abstract: The semisynthetic triterpenoid 2-cyano-3,12-dioxooleana-1,9(11)-dien-28-oic acid (CDDO) has several biological activities, including the induction of apoptosis in many cancer cell lines. To identify potential protein targets, immobilized biotinylated CDDO was used to screen the proteome of a human lymphoma cell line (U937) sensitive to CDDO-induced apoptosis. Tubulin was identified as one of several putative targets of CDDO. CDDO was shown to selectively bind to tubulin, with a dissociation constant of approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…At higher concentrations, CDDO-Im may bind to reactive cysteine residues on other target proteins, such as IKK, to induce apoptosis. Interestingly, all the direct targets of CDDO-Im and its analogues identified to date, including PPARg, Keap1, and h-tubulin, contain reactive cysteine residues, which play a critical role in the cellular function of the respective proteins (4,18,22). In our current studies, we have identified Cys 179 on IKK as a critical target of CDDO-Im.…”
Section: Discussionmentioning
confidence: 59%
“…At higher concentrations, CDDO-Im may bind to reactive cysteine residues on other target proteins, such as IKK, to induce apoptosis. Interestingly, all the direct targets of CDDO-Im and its analogues identified to date, including PPARg, Keap1, and h-tubulin, contain reactive cysteine residues, which play a critical role in the cellular function of the respective proteins (4,18,22). In our current studies, we have identified Cys 179 on IKK as a critical target of CDDO-Im.…”
Section: Discussionmentioning
confidence: 59%
“…Mitochondrial glutathione , the mitochondrial protease Lon (Bernstein et al, 2012), and a limited number of thiolcontaining mitochondrial proteins (Brookes et al, 2007) have also been studied using a biotinylated triterpenoid. The SOs also directly interact with tubulin and actin (Couch et al, 2006;, but the physiological consequences of these interactions are less apparent because very high concentrations of SOs (30 -50 M) are required to disrupt polymerization of these proteins. Moreover, mere interaction of a protein with a biotinylated SO does not ensure functionality.…”
Section: H Thiol Proteomementioning
confidence: 99%
“…To test whether CDDO forms adducts with Lon, we used a biotinylated conjugate of CDDO (CDDO biotin ), which has comparable activity to its parent compound albeit with reduced potency, 26,40 and which colocalizes with mitochondria. 22 CDDO or CDDO biotin were first reacted with SA-sepharose, and then combined with purified Lon.…”
Section: Cddo Interacts Directly With Purified and Cellular Lonmentioning
confidence: 99%
“…[24][25][26][27][28] We show that Lon is substantially upregulated in human malignant B-cell lymphoma patient samples and cell lines compared with resting or activated normal donor peripheral blood B cells. We also show that CDDO and its derivatives directly and selectively inhibit Lon-mediated proteolysis.…”
Section: Introductionmentioning
confidence: 99%